Susceptibility of different life stages of Tenebrio molitor (Coleoptera: Tenebrionidae) to indigenous entomopathogenic fungi. (September 2022) - Eski, Ardahan; Murat Gezgin, Muhammed
Abstract: Tenebrio molitor L, known as the yellow mealworm, is a polyphagous insect that infests cereals, flour, bran, and pasta worldwide. Both larvae and adults of the pest cause significant damage to stored products. In this study, entomopathogenic fungi were isolated from soil samples using the Tenebrio-bait method and the susceptibility of different life stages of T. molitor to these indigenous isolates was investigated. Based on morphology and nuclear ribosomal internal transcribed spacer (ITS) sequence, a total of seven fungal isolates, one Beauveria bassiana and six Metarhizium anisopliae, were identified. The screening test showed that the virulence of entomopathogenic fungi varies according to fungal species and strain, and that different life stages differ in their susceptibility to fungal infection. B. bassiana BL8 was the most effective isolate for all life stages tested. While adults were the most resistant life stage (LC50  = 5.6 × 10 6 conidia/ml) to B. bassiana infection, pupae were the most susceptible life stage (LC50  = 3.9 × 10 2 conidia/ml). The results show that B. bassiana BL8 is a promising microbial control agent that can support the control of T. molitor. Highlights: Seven indigenous entomopathogenic fungi were isolated by Tenebrio -bait method. B. bassiana BL8 caused 100% mortality on 4th, 10th and 16th instar larvae of T. molitor at 10 7 conidia/ml concentration. B. bassiana BL8 caused 65% mortality on T. molitor adults at 10 7 conidia/ml concentration. The lowest LC50 value for B. bassiana BL8 was observed in pupal stage as 3.9 × 10 2 conidia/ml.